Finding God in the Lord of the Rings - Bruner, Kurt (Tyndale House Publishers, 2021)
"The bestselling book now revised and updated with new content! Hailed as the most popular and best-loved series of the twentieth century, The Lord of the Rings trilogy is more than a great story; it's a reflection of life's epic quest for all of us. Examining the Christian themes in J.R.R. Tolkien's masterwork, bestselling authors Kurt Bruner and Jim Ware reveal a rich tapestry of hope, friendship, redemption, and faith in the face of overwhelming odds. - More than 200,000 copies sold - Includes six new chapters and a discussion guide - A helpful resource for personal study, devotions, or group discussion"--